A Study of the Factors Leading to the Adoption of Open-Source Software - Wong, Chun-Ying (2007)
As the breadth and quality of open-source software (OSS) grows, more abd more companies are faced with a decision of wether to use OSS or not. In this region, the imperative to minimize IT costs, specifically the cost of software, makes OSS an attractive proposition. This paper attempts to understand the factors that lead companies to adopt OSS. It discusses the advantages of OSS development method and the challenges in evaluating OSS. A module of the factors for OSS adoption is developed, which considers both rational and psychological issues relevant.